URGENSI KARAKTERISTIK MASYARAKAT ISLAM DALAM PERSPEKTIF AL-QUR’AN - Syarifuddin; Supi Amaliah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
The purpose of this study is to analyze the meaning of the characteristics of Islamic society in the perspective of the Al-Qur'an Karim. The research method used is a qualitative library approach. The source of research data is based on the book of interpretation of the Al-Qur'an, hadith, journal articles and books related to the research theme. The conclusion of the study is that Islam is a solution-oriented religion and its adherents are a community that has a strong grip, namely faith, civilization, balance and non-apartheid. This community is truly able to maintain a good life, full of peace and tranquility, guarantee the welfare of its members, and even provide happiness in two places, the world and the hereafter. This short article contributes a little in explaining the characteristics of Islamic society as described in the Al-Qur'an and has been practiced by the Prophet and his companions in the early days and then developed to the Arabian peninsula and its surroundings that to all corners of the world.